Bolsonarism´s hammers: essay on literature and the cis-heterosexist drone - Afonso-Rocha, Rick (Nomadías, 2024)
I will try to outline some considerations about literary enunciation, in terms of its versatile emergence on the discursive stage. It is an emergence traversed by the node (ideological/imaginary – political/symbolic – economic/real) that signifies it, determining meanings and controlling its affective functioning. I intend to highlight that literature, as part of the commercial apparatus, does nothing more than make subjects see and emerge readers, authors, characters, editors, consumers, integration, and realization. Next, I will present my analysis of Philip K. Dick’s literary statement The Governing Machine, for what it makes me see and makes me state in its complex meaning that, although not a priori, it can have directions impregnated in the form-subject in the one I recognize. That said, I need to anticipate what that statement makes me see and makes me say: the functioning of Bolsonarism as a technical machine of capital, from the drone in the cutting of the sex-gender system, which here I called the cis-heterosexist drone. I am interested in understanding the enunciative functioning (making people see/making people say) as an ideological, political, and economic paradigm, as a technical machine of the war machine of capital, that is, as a paradigm that goes beyond the Brazilian social formation, but that, At the same time, it carries certain singularities from the periphery of the world-system.